The Role of G Protein beta 3 Subunit Polymorphisms C825T, C1429T, and G5177A in Turkish Subjects with Essential Hypertension - FAK, ALİ SERDAR; NACAR, CEVDET; CABADAK, HÜLYA; ORUN, OYA (TAYLOR & FRANCIS INC, 2011)
Hypertension is a multifactorial disorder that constitutes a major risk factor for the cardiovascular system. Heterotrimeric G-proteins, which couple receptors for diverse extracellular enzymes or ion channels, are correlated with disease mechanisms. Several studies have demonstrated an association between G protein polymorphisms and essential hypertension in some populations, although contradictive results also exist. In this study, we have investigated the potential role of the C825T, C1429T, and G5177A polymorphisms of the beta 3 subunit of G-proteins in essential hypertension in a group of Turkish subjects. Genomic DNA from 106 normotensive individuals (117.4 +/- 13.1, 75.2 +/- 10.5; systolic blood pressure (SBP) and diastolic blood pressure (DBP) levels, respectively) and 101 hypertensive subjects (152.3 +/- 18.0, 92.5 +/- 11.6; SBP and DBP levels, respectively) were studied by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and direct sequencing methods for these polymorphisms. Allele frequencies of the polymorphisms were consistent with Hardy Weinberg equilibrium, except for the C825T polymorphism (chi(2) = 7.8). The frequencies of the 825T and 1429T variants were higher in hypertensive subjects compared to those of controls. Differences between hypertensives and controls were not statistically significant, though difference was very close to significance for C825T (p = 0.056 and 0.099 for 825T and 1429T, respectively). T allele frequency in overall population showed significant association with hypertension for C825T (0.0134). The prevalence of the 5177A-variant was very low and all subjects carrying it were heterozygotes in both groups.
Keywords: blood pressure; GNB3; hypertension; polymorphism; Turkish; HIGH BLOOD-PRESSURE; GENE GNB3; ETHNIC DISTRIBUTION; 825T ALLELE; ASSOCIATION; VARIANT; CHINESE; OBESITY